A unified lead-oriented synthesis of over fifty molecular scaffolds. Issue 3 (18th November 2014) - Doveston, Richard G.; Tosatti, Paolo; Dow, Mark; Foley, Daniel J.; Li, Ho Yin; Campbell, Amanda J.; House, David; Churcher, Ian; Marsden, Stephen P.; Nelson, Adam
Abstract : Sourcing large numbers of lead-like compounds is a major challenge; a unified synthetic approach enabled the efficient synthesis of 52 diverse lead-like molecular scaffolds from just 13 precursors. Abstract : Controlling the properties of lead molecules is critical in drug discovery, but sourcing large numbers of lead-like compounds for screening collections is a major challenge. A unified synthetic approach is described that enabled the synthesis of 52 diverse lead-like molecular scaffolds from a minimal set of 13 precursors. The divergent approach exploited a suite of robust, functional group-tolerant transformations. Crucially, after derivatisation, these scaffolds would target significant lead-like chemical space, and complement commercially-available compounds.